Attention Deficit Hyperactivity Disorder Treatment Practice in Turkey - Turkcapar, Mehmet Hakan; Oner, Ozgur; Isli, Fatma; Karadag, Hasan; Akbulat, Akif; Aksoy, Mesil; Basci, Ali Boray; Seckin, Cem; Alkan, Ali (KURE ILETISIM GRUBU A S, 2016)
Objective: To determine the factors associated with type of ADHD prescription and re-admission of the cases to the outpatient clinics between January-July 2013. Method: The Ministry of Health prescription database, which included prescriber, region, age and gender data and contained almost 20% of IMS data. Results: A total of 73,189 prescription were prescribed to a total of 41,341 (30,014 males; 72.7%) patients. 38645 (93.5%) of the patients were between 6 and 18 years of age. The most frequently prescribed drug was OROS methylphenidate (MPH, 59.7%) followed by IR MPH, atomoxetine and combination of drugs. There were several regional differences in prescription practice. Treatment choice changed significantly with age and gender. Rate of repeated prescription was highest among 6-18 year-old male subjects receiving combination treatment. Conclusions: ADHD treatment choice seemed to be heavily influenced by official regulations. Age, gender and drug of choice were important factors associated with treatment adherence
Keywords: ADHD; treatment; OROS; methylphenidate; atomoxetine